Direct and indirect spino-cerebellar pathways: shared ideas but different functions in motor control - Juan eJiang; Eiman eAzim; Carl-Fredrik eEkerot; Bror eAlstermark (Frontiers in Computational Neuroscience, 2015)
The impressive precision of mammalian limb movements relies on internal feedback pathways that convey information about ongoing motor output to cerebellar circuits. The spino-cerebellar tracts (SCT) in the cervical, thoracic and lumbar spinal cord have long been considered canonical neural substrates for the conveyance of internal feedback signals. Here we consider the distinct features of an indirect spino-cerebellar route, via the brainstem lateral reticular nucleus (LRN), and the implications of this pre-cerebellar ‘detour’ for the execution and evolution of limb motor control. Both direct and indirect spino-cerebellar pathways signal spinal interneuronal activity to the cerebellum during movements, but evidence suggests that direct SCT neurons are mainly modulated by rhythmic activity, whereas the LRN also receives information from systems active during postural adjustment, reaching and grasping. Thus, while direct and indirect spino-cerebellar circuits can both be regarded as internal copy pathways, it seems likely that the direct system is principally dedicated to rhythmic motor acts like locomotion, while the indirect system also provides a means of pre-cerebellar integration relevant to the execution and coordination of de